ANALISIS STRUKTUR GEDUNG IRNA (INSTALASI RAWAT INAP) RUMAH SAKIT UMUM PASAMAN BARAT MENGGUNAKAN SNI BETON BERTULANG 2847:2019 DAN SNI GEMPA 1726:2019 - Hamdeni Medriosa; Fikri Azida Akbar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Indonesia continues to follow the development of building standards in the world which are dynamically changing for the better and safer, both in loading regulations, planning for concrete structures, steel structures, and planning for earthquake resistance. The latest planning standard methods reviewed in this study are SNI-03-1726-2019, SNI-03-2847-2019 and RSNI-03-1727-2020 replacing SNI-03-1726-2012, SNI-03-1727-2013, and SNI-03-2847-2013. The basic difference in SNI-03-1726:2012 compared to SNI-03-1726:2019 is in the coefficients of Fa and Fv, namely the coefficient of soil sites for a long earthquake period of 1 second and in SNI-03-2847:2019 which refers to ACI 318M-14 Building Code Requirements for Structural Concrete. The results of this study found that this change in the modeling of the West Pasaman Regional General Hospital met the requirements for the SNI-03-1726-2019 earthquake design and the SNI-03-2847-2019 reinforced concrete design.